Glial glutamate transporters expression, glutamate uptake, and oxidative stress in an experimental rat model of intracerebral hemorrhage. (June 2018) - Neves, J.D.; Vizuete, A.F.; Nicola, F.; Da Ré, C.; Rodrigues, A.F.; Schmitz, F.; Mestriner, R.G.; Aristimunha, D.; Wyse, A.T.S.; Netto, C.A.
Abstract: Glial glutamate transporters (EAAT1 and EAAT2), glutamate uptake, and oxidative stress are important players in the pathogenesis of ischemic brain injury. However, the changes in EAAT1 and EAAT2 expression, glutamate uptake and the oxidative profile during intracerebral hemorrhage (ICH) development have not been described. The present study sought to investigate the changes of the above-mentioned variables, as well as the Na + /K + -ATPase and glutamine synthetase activities (as important contributors of glutamate homeostasis) and the percentage of neuronal cells after 6 h, 24 h, 72 h and 7 days of ICH. An injection of 0.2U of bacterial collagenase in the ipsilateral striatum was used to induce ICH in male Wistar rats; naïve animals were used as controls. EAAT1 and EAAT2 expression and glutamate uptake in the ipsilateral striatum were assessed. Additionally, the percentage of MAP2+ cells, Na + /K + -ATPase and GS activities, as well as the oxidative profile were analyzed. It is shown a decrease of EAAT1 expression and glutamate uptake 6 h post-ICH, whereas EAAT2 decreased 72 h after the event; conversely EAAT2 and glutamate uptake were increased after 7 days. The oxidative stress and endogenous defense system exhibited a remarkable response at 72 h of injury. ICH also increased Na + /K + -ATPase activity and selectively decreased GS activity, variables known to be important contributors of glial glutamate transporters activities. Altogether, present findings indicate that ICH induces different temporal EAAT1 and EAAT2 responses, culminating with an imbalance of glutamate uptake capacity, increased oxidative stress and sustained neuronal loss. Highlights: ICH induces different temporal EAAT1 and EAAT2 expression in the first week after injury. ICH causes glutamate uptake imbalance, increased oxidative stress and sustained neuronal loss. ICH increase Na + /K + -ATPase and decrease GS activity, both contributors of glial glutamate transporters activities.